Respostas
respondido por:
2
Lembrando da fórmula:
(a - b)³ = a³ - 3a²b + 3ab² - b³
(a + b)³ = a³ + 3a²b + 3ab² + b³
Vamos calcular:
(3p + q)³ = (3p)³ + 3.(3p)².q + 3.(3p).(q)²+ q³
= 27p³ +3.9p².q + 3.3p.q² + q³
= 27p³ + 27p²q + 9pq² + q³
(a - b)³ = a³ - 3a²b + 3ab² - b³
(a + b)³ = a³ + 3a²b + 3ab² + b³
Vamos calcular:
(3p + q)³ = (3p)³ + 3.(3p)².q + 3.(3p).(q)²+ q³
= 27p³ +3.9p².q + 3.3p.q² + q³
= 27p³ + 27p²q + 9pq² + q³
respondido por:
2
ola boa tarde !
(3p+q)^3 =>
(3p)^3+3×(3p)^2×q+3×3qp^2+q^3
27p^3+3×9p^2q+9pq^2+q^3
27p^3+27p^2q+9pq^2+q^3---->essa e a resposta !
espero ter ajudado e quando quiser disponha se ; )
(3p+q)^3 =>
(3p)^3+3×(3p)^2×q+3×3qp^2+q^3
27p^3+3×9p^2q+9pq^2+q^3
27p^3+27p^2q+9pq^2+q^3---->essa e a resposta !
espero ter ajudado e quando quiser disponha se ; )
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás